Property rights other than rights of ownership as an object of notarised transactions - O. Piddubnyi; O. Rohovenko (Law. Human. Environment, 2023)
The relevance of the subject is due to the frequency of application of property rights in practice, which led to the emergence of numerous situations when subjects applied to the court to protect their rights. The purpose of the study is to analyse the Ukrainian legislation on property rights other than property rights and to examine them as an object of notarisation. For the search, processing, and presentation of Information, special legal (comparative-legal, formal-legal, and the method of interpretation) and general scientific (formal-logical, analysis, synthesis, concretisation and abstraction, induction and deduction) methods are used. Considering the best practices of judicial practice, the concept of “waiting right” is fixed, which is directly related to objects of construction in progress. The shortcomings contained in the current Civil Code of Ukraine are identified. Attention is drawn to the fact that the planned re-modification of the code will correct many shortcomings existing in the private law sector of legal regulation. The correlation between the concepts of rights of ownership and property rights is outlined, and the absence of regulation of the concept of “property rights” in the Civil Code of Ukraine is stated. The study highlights the state of affairs regarding the notarisation of property rights other than rights of ownership. Changes caused by the entry into force of the Law of Ukraine “On Guaranteeing Rights of Ownership to Real Estate Objects That will be Built in the Future” were reported, and its importance for the regulatory plane, in general, are assessed. The problem of definitions of “property rights” and “rights of ownership” is examined. The scientific achievements of outstanding legal researchers are used, whose work is related to the correction of gaps contained in civil legislation, and the problems of insufficient definition of essential terms in regulatory legal acts regulating issues related to the subject under study. The specific features of using property and personal non-property rights in the field of intellectual property are established. The results of the study can be used for further development of doctrinal approaches to improving the institutions of property and rights of ownership.